The chromosome-level genome provides insights into the adaptive evolution of the visual system in Oratosquilla oratoria - Daizhen Zhang; Xiaoli Sun; Lianfu Chen; Lianyu Lin; Chijie Yin; Wenqi Yang; Jun Liu; Qiuning Liu; Huabin Zhang; Senhao Jiang; Yongxin Li; Boping Tang; et al. (BMC Biology)
Abstract Background The marine crustacean Oratosquilla oratoria is economically significant in seafood and aquaculture industries. However, the lack of high-quality genome assembly has hindered our understanding of O. oratoria, particularly the mechanisms underlying its developed visual system. Results We generated a chromosome-level genome assembly for O. oratoria (2.97 Gb, 44 pseudo-chromosomes) using combination sequencing strategies. Our analysis revealed that more than half of the genome was covered by repeat sequences, and LINE elements showed significant expansion. Furthermore, phylogenetic analysis revealed a close relationship of O. oratoria with Dendrobranchiata and Pleocyemata. In addition, the evolutionary rate of O. oratoria was slightly faster than that of Dendrobranchiata and slower than that of Pleocyemata. Interestingly, we observed the significant expansion of middle-wavelength-sensitive (MWS) opsins in the O. oratoria genome by tandem duplication, partially contributing to their unique visual capabilities. Compared with other crustaceans, O. oratoria has evolved a thicker cornea that was possibly driven by visual adaptations and ecological requirements. Employing comparative transcriptome analysis, we identified a tandemly duplicated cuticle protein (CP) cluster that was specifically expanded and expressed in the ocular tissues of O. oratoria, potentially contributing to the thick cornea of O. oratoria. Conclusions Our study established the first chromosome-level genome for Stomatopoda species, providing a valuable genomic resource for studying the molecular mechanisms underlying the developed visual system of O. oratoria.